Kruskall Wallis Test Pada Pengukuran Perbedaan Kelelahan Kerja Pada 3 Kelompok Tenaga Kerja Di Institusi Kependidikan - Rahmi Susanti; Irma Yanti; Windi Eka Saputri (coba, 2018)
This study attempts to knows the difference the rate of fatigue work in three professions different jobs.This research used the cross sectional the researchers conducted measurement and research at one time.The research was done in public health faculty of, mulawarman university, samarinda.Sample pegambilan in purposive sampling, sample were 12 people consisting of 3 professions work that is lecturers, tendik a and tendik b.Tendik a consisting of the part of life, academic and laboratory while tendik b is the official cleanliness.The measurement of fatigue work done in mid keja ( of time a break ).The measurement of use gauges fatigue work that is, reaction timer.The measurement of a performed in a time with the frequency of the measurement 20 times. The measurement results used are, measurement 4 to 17 which is then averaged. Statistical tests show that, there is a difference in the level of work fatigue at least one type of job profession (H count = 10002, c2 tables = 5,991). Based on the results of work fatigue measurement using reaction timer, no severe work exhaustion was found between the three professions, and the highest level of work fatigue was experienced by one B tendik worker with an average measurement of 466, 96 milliseconds which was categorized as moderate work fatigue.